2021
DOI: 10.1177/00202940211003926
|View full text |Cite
|
Sign up to set email alerts
|

Research on predictive sliding mode control strategy for horizontal vibration of ultra-high-speed elevator car system based on adaptive fuzzy

Abstract: In order to effectively suppress horizontal vibration of the ultra-high-speed elevator car system. Firstly, considering the nonlinearity of guide shoe, parameter uncertainties, and uncertain external disturbances of the elevator car system, a more practical active control model for horizontal vibration of the 4-DOF ultra-high-speed elevator car system is constructed and the rationality of the established model is verified by real elevator experiment. Secondly, a predictive sliding mode controller based on adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…For high-speed elevators, safety and ride comfort are important considerations for modern, high-quality elevators. However, increasing the lifting speed can bring about serious vibration problems, making passengers feel uncomfortable and physiologically fatigued, thus reducing the comfort of passengers and even affecting the service life of the lift as well as the safety of passengers travelling on the lift (Wang et al, 2021;Yang et al, 2014). Previous research results show that when the lift speed exceeds 3 m/s, the transverse vibration acceleration of the lift car will be significantly greater than that of the low-speed lift (Zhang et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…For high-speed elevators, safety and ride comfort are important considerations for modern, high-quality elevators. However, increasing the lifting speed can bring about serious vibration problems, making passengers feel uncomfortable and physiologically fatigued, thus reducing the comfort of passengers and even affecting the service life of the lift as well as the safety of passengers travelling on the lift (Wang et al, 2021;Yang et al, 2014). Previous research results show that when the lift speed exceeds 3 m/s, the transverse vibration acceleration of the lift car will be significantly greater than that of the low-speed lift (Zhang et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…By utilizing a sliding mode observer-based stator current and disturbance observer, the system's robustness is further improved, as evidenced by successful experimental results. Wang et al [16] delved into predictive SMC for horizontal motion systems. While the details are not directly related to cascade control, they provide insights into MPC strategies and applications.…”
Section: -Introductionmentioning
confidence: 99%
“…In [24], an adaptive sliding-mode controller with diffuse switching gain (FGASMC) is proposed to reduce the severe horizontal vibration of the high-speed elevator car system that is caused by the excitation of the guide rail. In [25], an adaptive fuzzy-based sliding-mode predictive controller (PSMC-AF) is presented to reduce the horizontal vibration of the ultra-high-speed elevator car system. Numerical simulations are presented considering some representative excitations of the guide rail and demonstrated that the proposed active control is more effective than the passive system.…”
Section: Introductionmentioning
confidence: 99%